Science policy frameworks for a post-pandemic green economic recovery - Zachariadis, Theodoros; Giannakis, Elias; Taliotis, Constantinos; Karmellos, Marios; Fylaktos, Nestor; Howells, Mark; Blyth, Will; Hallegatte, Stéphane (My University, 2023)
As current production and consumption patterns exceed planetary boundaries, many leaders have stressed the need to adopt green economic stimulus policies in the aftermath of the COVID-19 pandemic. This paper provides an integrated multi-stakeholder framework to design an economic recovery strategy aligned with climate stabilisation objectives. We first employ quantitative energy and economic models, and then a multi-criteria decision process in which we engage social actors from government, enterprises and civil society. As a case study, we select green recovery measures that are relevant for a European Union country and assess their appropriateness with numerous criteria related to climate resilience and socio-economic sustainability. Results highlight trade-offs between immediate and long-run effects, economic and environmental objectives, and expert evidence and societal priorities. Importantly, we find that a ‘return-to-normal’ economic stimulus is environmentally unsustainable and economically inferior to most green recovery schemes.
Keywords: Climate-compatible growth; Energy systems model; Input-output model; Multi-criteria decision analysis; Stakeholder engagement; Sustainable development goals